Effects of transdermal oestrogen replacement therapy on interleukin-6 production in postmenopausal women - Rachoń, Dominik; Myśliwska, Jolanta; Suchecka-Rachoń, Krystyna; Hak, Łukasz (Menopause Review/Przegląd Menopauzalny, 2002)
Objective: To investigate the influence of transdermal oestrogen replacement therapy on interleukin-6 (IL-6) production in postmenopausal women. Design: Prospective study. Materials and Methods: Both the serum levels and spontaneous IL-6 production by peripheral blood mononuclear cells (PBMC) in postmenopausal women were measured before and after 6 and 12 months of HRT using the B9 hybrydoma bioassay. The subjects were 50 healthy postmenopausal women who were divided into two groups. The HRT group (n=30) started receiving transdermal oestrogen (17β-oestradiol 50 μg/day) with a 10 day progestogen regimen (oral medroxyprogesteron acetate 10 mg/day). The control group consisted of 20 women who did not agree to HRT. Results: At baseline, women from both groups had similar mean IL-6 levels in the sera and PBMC cultures. After 12 months, serum IL-6 levels were significantly lower among women from the HRT group compared to the control group (p<0.05). HRT also decreased spontaneous IL-6 production by PBMC after 12 months (p<0.05). Conclusions: Our results indicate that transdermal oestrogen replacement therapy decreases IL-6 production among postmenopausal women. This effect may contribute to the antiatherogenic properties of oestrogens.